Analysis of Student Confidence in Performing Volleyball Bottom Serves in Elementary School - Nadia Jely Hernawati; Adang Sudrazat; Rizal Ahmad Fauzi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to analyze elementary school students’ confidence in performing volleyball underhand serves and to identify the factors influencing their confidence during physical education learning. The study employed a qualitative descriptive approach with a case study design. The participants consisted of five elementary school students, one physical education teacher, and one parent from SDN Pasirbiru. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using NVivo software through coding, data reduction, data presentation, and conclusion drawing. The findings revealed that students’ confidence levels were categorized into high, moderate, and low levels. Students with high confidence demonstrated greater participation, courage to perform underhand serves, and persistence when encountering difficulties. In contrast, students with low confidence tended to be passive, hesitant, and afraid of making mistakes during learning activities. The study also identified several factors influencing students’ confidence, including self-belief, emotional control, teacher support, peer support, and the learning environment. The novelty of this study lies in its focus on the psychological aspects of elementary school students in volleyball learning, particularly confidence in performing underhand serves. The findings indicate that supportive and enjoyable physical education learning environments can enhance students’ confidence and participation in volleyball activities.